2014
DOI: 10.1111/1469-0691.12410
|View full text |Cite
|
Sign up to set email alerts
|

Acute renal failure associated with vancomycin and β-lactams for the treatment of osteomyelitis in diabetics: piperacillin–tazobactam as compared with cefepime

Abstract: Few data are available on the nephrotoxic potential of vancomycin when combined with certain β-lactam antibiotics for the treatment of osteomyelitis (OM). A retrospective cohort study was conducted of all diabetic patients with OM treated with vancomycin plus piperacillin-tazobactam (VPT) or vancomycin plus cefepime (VC) for at least 72 h at a VA Medical Center between 1 January 2006 and 31 December 2011. All patients with a creatinine clearance (CrCl) of ≤ 40 mL/min, a blood urea nitrogen/serum creatinine (SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
84
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 24 publications
5
84
2
Order By: Relevance
“…A previous study completed at the VA St Louis Health Care System revealed high rates of PT prescribing with increasing cases of acute renal failure (ARF) (defined as a 50 % increase or 0.5 mg dl 21 increase in serum creatinine from baseline) (Moenster et al, 2014). Based on these data, the decision was made on 15 July 2012 to place PT on 72 h restriction, meaning that any inpatient provider could order the antibiotic, but each order would be given a 72 h stop date.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study completed at the VA St Louis Health Care System revealed high rates of PT prescribing with increasing cases of acute renal failure (ARF) (defined as a 50 % increase or 0.5 mg dl 21 increase in serum creatinine from baseline) (Moenster et al, 2014). Based on these data, the decision was made on 15 July 2012 to place PT on 72 h restriction, meaning that any inpatient provider could order the antibiotic, but each order would be given a 72 h stop date.…”
Section: Introductionmentioning
confidence: 99%
“…45 This finding with piperacillin-tazobactam is not surprising as its nephrotoxicity risk appears to be more significant than previously appreciated. [46][47][48][49] We do not believe that the tobramycin was the cause of the AKI alone in our case, but rather a contributing factor. Our patient experienced significant post-operative hypotension for a brief time period and was also on intravenous vancomycin.…”
Section: 32-35mentioning
confidence: 72%
“…One study comparing the use of vancomycin with piperacillin/ tazobactam and vancomycin with cefepime found higher incidence of acute renal failure in patients given both vancomycin and piperacillin/tazobactam than with cefepime; however, no statistical significance was demonstrated [8]. Because both antibiotics are eliminated through renal mechanisms and show nephrotoxicity individually, it is predicted that the concomitant use of vancomycin and piperacillin/tazobactam can cause a higher incident of nephrotoxicity than when used as monotherapy [1,2,8].…”
Section: Introductionmentioning
confidence: 99%
“…Acute renal failure can be defined as serum creatinine (SCr) increase by 0.5 mg/dL or increase by 50% from baseline [8]. In a person without any kidney disease, serum creatinine is constant with very small variability [9].…”
Section: Introductionmentioning
confidence: 99%